An approach to teaching the particle-wave duality of light - Brillante, Cesar S. (s.n.], 1968)
The study presented an approach to the teaching of the dualism of light: the particle theory and the wave theory. The seminar paper presents old evidences for each theory in a new way. Thus, by utilizing what is considered effective in the traditional method and by introducing modernized methods and techniques, knowledge of the nature and behavior of light will be better understood by the students.